Analysis of the Preparedness of the Sibakul Jogja Program as a Post-COVID-19 Economic Strengthening Effort for Micro, Small, and Medium Enterprises in the Special Region of Yogyakarta - Nurmaghfiroh, Elma Fadhilah; Atmojo, Muhammad Eko (Jurnal Studi Ilmu Pemerintahan, 2023)
This study aims to describe the preparation of the SiBakul Jogja program, one of the DIY Cooperative and UKM Service's assisted programs, to revive the MSME actors' economy in DIY during the post-Covid-19 pandemic. This study used a qualitative descriptive research method with a case study approach, namely the SiBakul Jogja case study. In this research, data collection techniques using interviews and documentation techniques. Data collection through interview techniques with Entrepreneurship Staff at the DIY PLUT Consultant Coordinator section and six MSME actors who are members of the SiBakul Jogja application with different categories is intended to obtain primary data or basic data as keywords in this study. While documentation techniques are used to obtain secondary data from previous research, online news, journals and official government channels, and other additional data to strengthen primary data. The results of this study explain that of the five indicators in preparation for the SiBakul Jogja program during the post-Covid-19 pandemic, which was directly fostered by the DIY Cooperative and UKM Service for MSME actors in DIY, they were not fully prepared to fulfill the program preparation theory as developed by Hudson (1981)